Growth and survival of goldfish larvae, (Carassius auratus) L.fed with live and artificial feeds. - Ang, Kok Jee; Liew, W. C.; Cheah, S. H. (1987)
One week old goldfish larvae (12mg in weight) were studied in 12 aquarium tanks at a stocking density one larva per litre to determine the suitabilities of Artemia naulii,Moina,Egg custard and a commercial feed as their diet. At the end of the 8 weeks study,the mean weight of fry fed on Artemia ,Moina,egg custard and a commercial feed were 773mg,578mg,302mg and 148mg respectively. Fry fed on Artemia recorded the highest growth rate (p<0.05) as compared to the other diets, All diets differ significantly in weight (p<0.05). Live diets recorded 100% survival while egg custard and commercial feeds had a survival rates of only 61% and 11% respectively. The study shows the superiority of live feeds over prepared diets for goldfish fry rearing in terms of growth and survival rates. Though Artemia diet exhibited the best growth but Moina diet would be preferable as goldfish fry feed due to the high price of Artemia cysts.